Relations between tourism and sport in the context of tourism as an academic discipline - Kotus, Jacek (Turyzm/Tourism, 2016)
The specific objective of the paper is to discuss the mutual relations between tourism and sport and, in a wider context, to draw the reader’s attention to the potentially excessive range of research goals in tourism as a discipline. Within the scope of discussion, the author looks at tourism as a social activity and a conceptual and research subject. Research questions, the signposts of intellectual debate, come down to whether tourism shares any common areas with sport (in its widest sense). If so, is such activity still tourism activity? Or perhaps these types of ‘sport-tourist’ activities should be excluded from discussion on tourism as an academic discipline because of their non-tourist character? The author assumes that there is an exploratory and cognitive zone between these two areas of social activity, going beyond both tourism and sport. Tourist activity and sport activity in fact differ from each other.